A 14-year-old patient with Prader-Willi syndrome: a case report - Marlinna Marlinna; Madarina Julia; Noormanto Noormanto (Indonesian Pediatric Society, 2023)
Prader-Willi Syndrome (PWS) is a disorder resulting from a loss of genetic information on chromosome 15q11.2-q13 inherited from the father. It can be caused by paternal deletions (65-75%) or uniparental maternal disomy (20-30%). The prevalence of PWS is estimated to be 1/10,000 - 1/20,000 births.1 Although its incidence is relatively rare, PWS can cause major health problems for patients and decreased quality of life for their families. The course of PWS is characterized by severe hypotonia in the neonatal period, severe feeding problems resulting in growth failure, as well as small hands and feet. Hypogonadism manifests as genital hypoplasia, delayed puberty, and infertility. Children with PWS have delayed motor and language development. Most patients have some degree of intellectual disability. Hyperphagia and obesity occur in early childhood. The patient’s excessive eating behavior affects the patient’s and family’s quality of life, and is often responsible for high morbidity and mortality.